Satisfaction with sports services of University Campus of Espinardo - Nicolás-López, J.; Escaravajal-Rodríguez, JC. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
This study aims to determine the degree of user satisfaction with sports services University campus of Espinardo. The study involved 61 subjects of both sexes and with an age range between 18 and 66 years. A validated instrument was used for conducting the survey, "Assessment Questionnaire sports services (EPOD2)". The results show that customers show a high degree of satisfaction in virtually all dimensions analyzed. Paragraphs variety, modernity and maintenance of materials and possibilities of suggestions are those with a higher degree of dissatisfaction on the part of users of the facilities, although overall satisfaction level in these items remains greater than 50%. In conclusion, the satisfaction of users is very high, showing only needs to improve specific aspects of some dimensions.